2005
DOI: 10.1021/jo0510843
|View full text |Cite
|
Sign up to set email alerts
|

(+)- and (−)-2-Aminocyclobutane-1-carboxylic Acids and Their Incorporation into Highly Rigid β-Peptides:  Stereoselective Synthesis and a Structural Study

Abstract: [Chemical reaction: See text] Several derivatives of (+)- and (-)-2-aminocyclobutane-1-carboxylic acid, 1, have been prepared through enantiodivergent synthetic sequences. The stereoselective synthesis of free amino acid (+)-1 has been achieved, and this product has been fully characterized for the first time. Stereocontrolled alternative synthetic methodologies have been developed for the preparation of bis(cyclobutane) beta-dipeptides in high yields. Among them, enantio and diastereomers have been synthesize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 35 publications
4
48
2
Order By: Relevance
“…In contrast, the C‐terminal residue has equatorial C=O and axial NH groups ( θ = 61°), and participates in intermolecular hydrogen bonds, which result in infinite sheet‐like interactions along the crystallographic b axis. The hydrogen‐bonded packing pattern for 6 is different from those reported previously for homodimers of cis ‐2‐aminocycloalkanecarboxylic acids in the crystal state 20,21. The direction of the N‐ to the C‐terminus of 6 alternates along the packing direction, whereas cis ‐ACBC20 and cis ‐ACPC dimers21 are packed parallel along the direction of intermolecular hydrogen bonding.…”
Section: Resultscontrasting
confidence: 91%
“…In contrast, the C‐terminal residue has equatorial C=O and axial NH groups ( θ = 61°), and participates in intermolecular hydrogen bonds, which result in infinite sheet‐like interactions along the crystallographic b axis. The hydrogen‐bonded packing pattern for 6 is different from those reported previously for homodimers of cis ‐2‐aminocycloalkanecarboxylic acids in the crystal state 20,21. The direction of the N‐ to the C‐terminus of 6 alternates along the packing direction, whereas cis ‐ACBC20 and cis ‐ACPC dimers21 are packed parallel along the direction of intermolecular hydrogen bonding.…”
Section: Resultscontrasting
confidence: 91%
“…In an extension to our photocycloaddition methodology, we wanted to expand the range of available products through further synthetic transformations of the photoadducts. To this end, we found that cyclobutyl ester 7 h (EWG=CO 2 t Bu) is a particularly useful photoproduct, which can be selectively transformed in excellent yield into the corresponding free acid 14 23 or alcohol 15 (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…Short peptide sequence like dipeptide sequences containing trans-AC 4 C formed an eight-membered hydrogen bond 3 2. 33 but longer sequences(such as hexamer and octamer) of the trans-A~C were stabilized through a 12-membered hydrogen bond and adopted a 12-helical conformation both in the solid state and in the solution 34 • The aza analogue of the ACC was also synthesized on the assumption that it would behave similarly like ACC 56 • Further, it was hypothesized that the additional nitrogen atom in the ring could act as a hydrogen bond acceptor that could provide the extra stability in the peptides nucleating different folds. There is another example of a four membered P-amino acid that contains an oxetane ring 57 • The peptide hexamer ( Figure 6) containing this amino acid gave a 1 0-helix in solution as confirmed by 2D NMR studies.…”
Section: P-amino Acids With Four Membered Ringsmentioning
confidence: 99%